2017
DOI: 10.17140/pmhcoj-se-1-102
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Palliative Care in Palestine: Cultural and Religious Perspectives

Abstract: CitationAbu Seir A, Kharroubi A. Implementation of palliative care in palestine: Cultural and religious perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…However, feelings such as fear of death and dying are found equally among all people. Our study, similarly to an earlier study from the region (Abu Seir & Kharroubi, 2017), demonstrated that the basic principles of PC are independent of a patient's ethnic background, religion or culture. Medical professionals involved in this study had very different wishes regarding their own dying.…”
Section: Discussionsupporting
confidence: 88%
“…However, feelings such as fear of death and dying are found equally among all people. Our study, similarly to an earlier study from the region (Abu Seir & Kharroubi, 2017), demonstrated that the basic principles of PC are independent of a patient's ethnic background, religion or culture. Medical professionals involved in this study had very different wishes regarding their own dying.…”
Section: Discussionsupporting
confidence: 88%
“…According to Palestinian Bureau of statistics life expectancy for Palestinian males is 72.1 y and for females 75.2 y (statistics, 2016). Due to high fertility rate and high proportion of younger population, older Palestinian population ≥ 65 was only 2.9% of total population in 2000(Abu Seir & Kharroubi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant issue is the consistent shortage of medications at the governmental hospitals that patients are required to take home for their treatment. This is a persistent issue ( 12 , 28 ). Specifically, the lack of pain medications highlights the absence of a palliative care program in cancer care, confirmed by the oncologists participating in the study.…”
Section: Discussionmentioning
confidence: 99%